ANALISIS PROSEDUR PENCAIRAN DAN PENCATATAN KREDIT BAGI DOSEN DAN STAF UNIVERSITAS PAMULANG PADA BPR SEHAT SEJAHTERA - A’zzizah, Dewi; Anthoni, Lukman (Asosiasi Dosen Muda Indonesia, 2023)
Bank Perkreditan Rakyat (BPR) function as institutions that gather and channel funds to the public. They play a strategic role in supporting the implementation of national development that has an impact on improving the standard of living for the community. The objective of this research is to understand the credit disbursement procedures for lecturers and staff at Pamulang University in BPR Sehat Sejahtera and the accounting recording of credit disbursement for lecturers and staff at Pamulang University in BPR Sehat Sejahtera. This research uses a qualitative descriptive method aimed at understanding the procedures and policies for credit disbursement at BPR Sehat Sejahtera branch and the accounting recording of credit disbursement at BPR Sehat Sejahtera. Based on the research conducted at BPR Sehat Sejahtera, it is found that the credit disbursement procedures for lecturers and staff are quite good, involving several stages such as credit application, initial verification, feasibility analysis, credit committee, cash section, and credit administration. The accounting recording of credit disbursement is also generally good, but there are some aspects that need improvement, such as the calculation of interest and administrative fees